Analysing chronic spinal changes in ankylosing spondylitis: a systematic comparison of conventional x rays with magnetic resonance imaging using established and new scoring systems. Issue 9 (5th April 2004) - Braun, J; Baraliakos, X; Golder, W; Hermann, K-G; Listing, J; Brandt, J; Rudwaleit, M; Zuehlsdorf, S; Bollow, M; Sieper, J; van der Heijde, D
Abstract : Objectives: To compare conventional radiography and magnetic resonance imaging (MRI) for detection of chronic changes in the spine of patients with ankylosing spondylitis (AS). Methods: Assessment of chronic lesions in conventional x rays and T1 weighted MRI turbo spin echo sequences was performed with the established x ray scores BASRI and SASSS, the new Berlin score, and the MRI scoring system ASspiMRI-c All images were read twice and "blindly" by two readers. One vertebral unit (VU) was defined as the region between two virtual lines drawn through the middle of each vertebra. Definite involvement was defined as a score ⩾2 in a spinal segment. Results: Thirty nine patients with AS were examined (25 (64%) male, mean age 40.9 years, 33/36 (92%) HLA-B27 positive). The Berlin score correlated with the BASRI ( r  = 0.73, p = 0.01). The ASspiMRI-c correlated well with the BASRI and the Berlin score ( r  = 0.66 and r  = 0.51, respectively, p = 0.01). The Berlin x ray score showed that 12/35 (34.3%), 13/35 (37.1%), and 12/28 (31.6%) patients had definite involvement of the cervical spine (CS), thoracic spine (TS), and lumbar spine (LS), respectively. The ASspiMRI-c showed that 10/36 (27.8%), 21/36 (58.3%), and 9/35 (25.7%) patients had definite involvement of the CS, TS, and LS, respectively. Syndesmophytes were found in 14.4% of all VUs with 90% agreement between the SASSS and Berlin score. Conclusions: T1 weighted MRI can detect chronic lesions in AS. The two new scoring systems proved valid in comparison with established scoring systems and based on aspects of the OMERACT filter. The thoracic spine is most commonly affected in AS. This part of the spine is best assessed by MRI.